2018
DOI: 10.1002/sd.1847
|View full text |Cite
|
Sign up to set email alerts
|

Needs, wants and values in China: reducing physical wants for sustainable consumption

Abstract: China is simultaneously the world's biggest polluter, largest victim of pollution, and most ferocious fighter against pollution. So the question is: How can pollution be reduced to pave the way for the ecological civilisation of the future moderately affluent Chinese society? For China to play a leading role in escaping the global environmental crisis, for the benefit of its own population and the rest of the world, technological improvements and the greening of the economy, important as they are, will not suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Our world is suffering from severely environmental deterioration because of intricate causes. Green consumption, a typical pro‐environmental behavior, has been advocated as an effective response to the environmental crisis (Nguyen, Nguyen, & Hoang, ; Pagiaslis & Krontalis, ; Yan & Spangenberg, ). However, it is difficult to alter consumers' attitudes and behaviors (Nguyen et al, ), so that strategies are required to intervene and guide people to accept and adopt green consumption concept.…”
Section: Introductionmentioning
confidence: 99%
“…Our world is suffering from severely environmental deterioration because of intricate causes. Green consumption, a typical pro‐environmental behavior, has been advocated as an effective response to the environmental crisis (Nguyen, Nguyen, & Hoang, ; Pagiaslis & Krontalis, ; Yan & Spangenberg, ). However, it is difficult to alter consumers' attitudes and behaviors (Nguyen et al, ), so that strategies are required to intervene and guide people to accept and adopt green consumption concept.…”
Section: Introductionmentioning
confidence: 99%
“…The literature generally agrees that the people are satisfied with happiness as soon as social sustainability prevails. Yan and Spangenberg () stated that ensuring social justice and fair distribution is also an indispensable component of the happiness of the citizens and, hence, of political stability. Rogers et al () advocated that human well‐being is a more important factor in social sustainability when compared with consumption and called for the equitable distribution of natural resources for sustainable development.…”
Section: Introductionmentioning
confidence: 99%
“…Using a Chinese sample, Mi et al (2020) showed how differences in cultural values affect both private and public sphere pro-environmental behaviors. Religious and cultural values in eastern societies wield a significant influence human psyche and behavior (Jain, 2016;Yan & Spangenberg, 2018). Extending this to consumption choices, we hypothesize thus:…”
Section: Independent Effect Of Consumption Culture Dimensions On Sust...mentioning
confidence: 93%